Perceived Augmentation of Augmented Reality Features on Affective Response, Cognitive Response, and Purchase Intention: A Systematic Literature Review in the Context of Skincare Product on E-Commerce Platform - Syarifatul Insaniyah; Ika Diyah Candra Arifah (Universitas Negeri Surabaya, 2025)
This study explores how perceived augmentation of Augmented Reality (AR) features influences affective response, cognitive response, and purchase intention, with a specific focus on Somethinc products on e-commerce platforms. Utilizing a Systematic Literature Review (SLR) approach, Python-based bibliometric tools were employed to retrieve, clean, and analyze academic publications from databases such as Scopus, ScienceDirect, and IEEE Xplore. A total of 518 articles were initially identified using targeted keywords, and 58 met the inclusion criteria. Findings reveal consistent support for AR as a persuasive tool that enhances emotional engagement, mental processing, and ultimately drives purchase decisions—especially in the beauty and skincare industry. This review provides a foundation for future empirical research and offers theoretical and managerial implications in the domain of AR-driven social commerce.